An investigation of the interrelationships of leadership styles, psychological safety, thriving at work, and work engagement in the hotel industry: A sequential mediation model - Rabiul, Md Karim; Karatepe, Osman M.; Al Karim, Rashed; Panha, I. M. (Elsevier Sci Ltd, 2023)
Drawing on the transformational leadership (TL), self-concept, and servant leadership (SL) theories as well as the socially embedded model of thriving, our paper tests whether psychological safety and thriving at work mediate the effects of TL and SL on work engagement (WENG) sequentially. Data gathered from 294 hotel employees in Cambodia were utilized to gauge these associations via partial least squares structural equation modeling. Results suggest that psychological safety or thriving partly mediates the link between SL and WENG, while thriving is a partial mediator between TL and WENG. In congruence with the study predictions, psychological safety and thriving mediate the link between SL and WENG sequentially. On the contrary, TL is not significantly related to psychological safety, which does not contribute to the sequential mediation process. Using the aforesaid findings, implications are discussed, and future research directions are offered.
Keywords: Hotel employees; Leadership; Psychological safety; Thriving; Work engagement